(untitled) (International Journal of Engineering and Computer Science, 2015)
This proposes a space time block code orthogonal frequency division multiplexing downlink baseband receiver for mobile wireless metropolitan area network. The proposed baseband receiver applied in the system with two transmit antennas and one receive antenna aims to provide high performance in outdoor mobile environments. It provides a simple and robust synchronizer and an accurate but hardware affordable channel estimator to overcome the challenge of multipath fading channels. The coded bit error rate performance for 16 quadrature amplitude modulation can achieve less than under the vehicle speed of 120 km/hr. The proposed baseband receiver designed in 90-nmCMOS technology can support up to 27.32 Mb/s uncoded data transmission under 10MHz channel bandwidth. It requires a core area of mm and dissipates 52.00 mW at 78.4 MHz with 1 V power supply. Index Terms—Baseband receiver, channel estimator, space time block code-orthogonal frequency division multiplexing (STBC-OFDM) system, synchronizer, wireless metropolitan area network (WMAN).